2002
DOI: 10.2134/jeq2002.4440
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Heteroaromatic Nitrogen after Prolonged Humification of Vascular Plant Remains as Revealed by Nuclear Magnetic Resonance Spectroscopy

Abstract: In the search for the mechanisms involved in the immobilization of organic nitrogen in humified remains of vascular plants, the efforts of the present investigation were directed toward the examination of the transformation of nitrogenous compounds during the peat and coal stage by means of solid-state nuclear magnetic resonance (NMR) spectroscopy. While accumulation of heteroaromatic-N is not detected in most of the studied peat layers, a clear shoulder in the chemical shift region of pyrrole- or indole-N is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2003
2003
2010
2010

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 27 publications
2
14
0
Order By: Relevance
“…Knicker (2000) has referred to her NMR evidence that shows that > 80% of the organic N in soils is in peptide -like structures. Knicker et al (2002) did detect a clear shoulder in the chemical shift region for pyrrole -or indole -heteroaromatic N ( − 145 to − 220 ppm) in the 15 N -NMR spectrum of the deepest layer of a peat that was at least 10,000 years old. However, this peat could be considered to be at the beginning of the coalifi cation stage, and there is abundant evidence for heterocyclic N in coal.…”
Section: Soil Peptidesmentioning
confidence: 93%
“…Knicker (2000) has referred to her NMR evidence that shows that > 80% of the organic N in soils is in peptide -like structures. Knicker et al (2002) did detect a clear shoulder in the chemical shift region for pyrrole -or indole -heteroaromatic N ( − 145 to − 220 ppm) in the 15 N -NMR spectrum of the deepest layer of a peat that was at least 10,000 years old. However, this peat could be considered to be at the beginning of the coalifi cation stage, and there is abundant evidence for heterocyclic N in coal.…”
Section: Soil Peptidesmentioning
confidence: 93%
“…The identity of this amide functionality belongs to proteins and/or peptides but other amides such as amino sugars are also possible. In contrast, N-compounds in thermally mature sediments are generally considered to be of the pyridinic and aromatic form (Knicker et al, 2002;Boudou et al, 2008;Schimmelmann and Lis, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, incubations of plant material with 15 N-labeled urea (Benzing-Purdie et al 1992;Skene et al 1997) and humic fractions with 15 N-labeled nitrite (Thorn and Mikita 2000) formed considerable quantities of non-amide N. Incubations of soil with 15 N-labeled trinitrotoluene (TNT) also resulted in the formation of non-amide TNT-breakdown products containing various forms of organic N (Knicker et al 1999;Bruns-Nagel et al 2000;. Two types of organic matter in which the signal for heterocyclic N does constitute most of the 15 N NMR signal detected are chars (Derenne et al 1993;Knicker et al 1996b;Keleman et al 2002), including the char fraction of soil (Knicker and Skjemstad 2000), and fossil organic matter such as coal and kerogen Knicker et al 1996a;Keleman et al 2002;Knicker et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…This problem is expected to be more severe for 15 N CP NMR spectra, as the lower gyromagnetic ratio of the 15 N nucleus results in a weakening of the critical dipolar coupling responsible for polarization transfer. Furthermore, the short contact times of 1 ms or less that are usually employed to characterize organic N (see, for example, Knicker, 2000a, b;Knicker and Hatcher 2001;Knicker et al 2002) can bias the acquisition of signal intensity toward directly protonated nitrogen types such as amide, at the expense of that derived from non-protonated N. Keleman et al (2002) showed using model compounds that long contact times were required to acquire signal from non-protonated N efficiently. Furthermore, Keleman et al (2002) found that the detection of non-protonated N was sensitive to the magnetic field strength of the spectrometer.…”
Section: Introductionmentioning
confidence: 99%